A new species and a new species record of Hypogastrura (Collembola: Hypogastruridae) from China - Jiang, Jigang; Chen, Jian-Xiu (Zootaxa, 2008)
Hypogastrura distincta (Axelson, 1902) is recorded from China for the first time and a new species, Hypogastrura quadritenenta sp. nov., is described from Nanjing. Both species belong to the H. viatica group. The new species differs from all known members of the group by possessing 2, 4, 4 tenent hairs on tibiotarsi I–III, six setae on dens and a broad basal lamella on the unguiculus. A checklist and a key to Chinese species of the genus Hypogastrura are provided.